DEVELOPMENT OF CASHEW NUT PROCESSING MACHINE - OYETUNJI ROPO; AKINFENWA AYOBAMI; ADEWUYI FESTUS (Journal of Engineering Studies and Research)
The stress, injuries and hazardous effects incurred during processing of cashew nut is huge. This work considered the design and development of cashew nut processing machine to help farmers improve the process efficiency. Cashew nuts were fed into the machine containing the heating and shelling chamber. The designed machine dried, roast and shelled the nuts. The shelled cashew nuts were then cooled, and kernels separated from shell manually. An efficiency of 80% was determined in terms of number of whole kernel recovery, roasting and cracking time.